Prehospital tranexamic acid decreases early mortality in trauma patients: a systematic review and meta-analysis - Li, Yi; Tian, Mei; Zhong, Wen; Zou, Jiatong; Duan, Xin; Si, Haibo (Frontiers in Medicine, 2025)
BackgroundAs an anti-fibrinolytic agent, tranexamic acid (TXA) is widely recognized for its efficacy in managing hemorrhagic conditions. Prehospital application of TXA has been reported in recent years, but its benefits in trauma patients remain debated.Materials and methodsA literature search was conducted across databases including PubMed, Cochrane Library, Embase, Web of Science, SCOPUS, and the Cochrane Central Register for Clinical Trials from inception to October 2024, focusing on studies related to prehospital TXA and clinical outcomes in trauma patients. The Cochrane Risk of Bias 2 Tool was applied to assess the quality of randomized control trials (RCTs), while the Newcastle-Ottawa Scale was used for observational cohort studies. Data were pooled under a random- or fixed-effects model using RevMan 5.4 with odds ratio (OR) and 95% confidence interval (CI) as the effect measures.ResultsA total of 286 publications were identified from the initial database search, and 12 studies, including five RCTs and seven observational cohort studies with a total of 12,682 patients, were included. Significant early survival benefits were observed in patients receiving prehospital TXA compared to those not receiving prehospital treatment. Compared to the control group, the prehospital TXA group exhibited a significant reduction in 24-h mortality with an OR of 0.72 and a 95% CI of 0.54–0.94 (p = 0.02), while no statistically significant difference in the incidence of venous thromboembolism (VTE; OR: 1.14, 95% CI: 0.98–1.33, p = 0.09). No significant differences were observed in other outcomes, such as 28–30-day mortality, overall mortality, length of hospital stay, and the incidence of multiple organ failure (all p > 0.05).ConclusionPrehospital TXA decreases early (24-h) mortality in trauma patients without a significant increase in the risk of VTE and other complications, and further studies are still needed to improve and optimize its management strategy.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, Identifier: CRD 42019132189.